Ambiguity and contractual incompleteness. Issue 11 (25th June 2023) - Wang, Zile; Chen, Meichen; Qin, Xiangdong; Shi, Yufeng
ABSTRACT: We introduce ambiguous states into an experimental investigation of a tradeoff between contractual rigidity and flexibility. Ambiguity magnifies both parties' pessimism in an incomplete context. Ambiguity aversion is revealed in their choice. More complex interactions emerge in ambiguous environments.